Catalytic activity of magnetic iron oxide nanoparticles for hydrogen peroxide decomposition: optimization and characterization. Issue 9 (29th April 2020) - Maharjan, Anoth; Dikshit, Pritam Kumar; Gupta, Arvind; Kim, Beom Soo
Abstract: BACKGROUND: The present study is focused on the decomposition of hydrogen peroxide (H2 O2 ) using magnetic iron oxide nanoparticles (Fe3 O4 NPs). Intrinsic peroxidase mimicking activity of Fe3 O4 NPs helps in decomposition of H2 O2 for the generation of OH radicals during the Fenton process. A response surface methodology based central composite design (CCD) method was adopted to optimize five different process parameters: reaction time, temperature, pH, Fe3 O4 NP concentration and H2 O2 concentration. RESULTS: CCD‐predicted H2 O2 decomposition (%) showed close agreement with the experimental results, confirming the good fit of the experimental data to the model. A maximum H2 O2 decomposition of 92.31% was achieved with an initial H2 O2 concentration of 31.07 mg L −1, Fe3 O4 NPs of 1.34 wt%, pH of 5.29, temperature of 23.1 °C and reaction time of 5.6 min as optimal values. The morphology and structure of Fe3 O4 NPs before and after the reaction process were characterized using scanning electron microscopy, energy‐dispersive X–ray spectroscopy, Fourier transform infrared spectroscopy, X‐ray diffraction spectroscopy and thermogravimetric analysis. CONCLUSION: The characterization data showed no significant changes in the structure of Fe3 O4 NPs after the reaction compared to the pristine Fe3 O4 NPs. The catalytic efficiency of these NPs was found to be in close agreement with other similar materials reported in previous literature. These optimization variables for H2 O2 decomposition using Fe3 O4 NPs may be useful in designing protocols for practical application at a large scale. © 2020 Society of Chemical Industry